Efficiency in French Commercial Banks: A Stochastic Frontier Analysis - XIE, XINGMEI (2019)
The primary purpose of this paper is to estimate the efficiency of French commercial banks between 2011 and 2018. The main goal is to study the impact of various types of financial events on its cost efficiency based on the analysis of French bank efficiency before learning. The primary method used is the Random Frontier Method (SFA), which contains a large number of tests that support SFA, such as tests for testing the rate likelihood of SFA inefficiencies.